Analisis Potensi Pencemaran Air Tanah Di Sekitar TPA Kebon Kongok Dengan Uji MPN Bakteri Coliform - Mukminah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Water is an essential material in life, water is needed by living things, especially as drinking water. There are many factors that hinder or trigger the availability of clean water to decrease. One of these factors is human activities that can cause problems for the availability of clean water supply for healthy consumption of the community. One of these factors is the existence of a Final Disposal Site (TPA). The final disposal site (TPA) in West Lombok is the Kebon Kongok TPA. This research is a descriptive analytic study. This research was conducted at the Health Testing and Calibration Laboratory Center (BLKPK) of West Nusa Tenggara Province. Well water samples are taken directly at the location, then taken to the laboratory for examination in order to obtain primary data. Sample measurement was carried out using the MPN (Most Probable Number) method which was carried out at the West Nusa Tenggara BLKPK laboratory. Variety II: 5 x 10 ml, 5 x 1 ml, 5 x 0.1 ml. Variety 2 is used for specimens that have not been processed or are thought to have a high germ count. There were 12 samples of well water tested and all of them were positive for coliform bacteria. The number of Coliform bacteria found in the test samples varied. The highest number of bacteria was found in sample 1, which contained Coliform 5400/100 ml of water. This happens because the distance of sample 1 well is only 10 meters from the leachate or leachate waste collection point. All samples of well water tested were already at the threshold of clean water so they were not fit for consumption.